Parental Coordination of Chick Provisioning in a Planktivorous Arctic Seabird Under Divergent Conditions on Foraging Grounds - Grissot, Antoine; Araya-Salas, Marcelo; Jakubas, Dariusz; Kidawa, Dorota; Boehnke, Rafał; Błachowiak-Samołyk, Katarzyna; Wojczulanis-Jakubas, Katarzyna (Frontiers in Ecology and Evolution, 2019)
An increasing number of studies report coordinated chick provisioning by avian parents. Although the pattern of parental coordination varies across species, broad occurrence of this coordination suggests that it has an adaptive value: it may increase individual fitness via higher offspring survival, faster offspring growth rate and/or higher body reserves of the parents. However, to what extent the pattern of coordinated provisioning in a species represents a flexible response to current foraging conditions remains an open question. Here, we examined coordination of chick provisioning in the Little Auk (Alle alle), a planktivorous seabird species that breeds in the Arctic. Harsh environmental conditions impose bi-parental care on this species, and high variability within and across breeding seasons promotes flexibility in parental involvement to secure breeding success. During the chick rearing period, parents exhibit a dual-foraging strategy (i.e. alternating long foraging trips, serving to maintain the adults’ body reserves, with several short trips aimed to provision the chick). We examined coordination of parental provisioning across five breeding seasons varying in terms of environmental conditions and found that the parents indeed coordinate their provisioning, avoiding performing long trips simultaneously and thus enabling a more even distribution of feeding through time. We also examined chick body condition in relation to the level of parental coordination to test the potential adaptive value of coordination, but we found no significant relationship between these two parameters. We found high variability in the level of the coordination between pairs, and this variability was similar across all study seasons, which represented a wide range of experienced environmental conditions. Nevertheless, we found that the energy density of food loads delivered to chicks was associated with the level of parental coordination: when conditions were characterised by the delivery of higher-energy food loads, the level of coordination exhibited by the studied population was higher. These findings suggest that environmental conditions somehow affect parental coordination, but the range of the environmental variation could be still below a critical threshold of extreme conditions that would trigger more pronounced modifications of parental foraging patterns and coordination.